The A to Z of Malaysia - Ooi, Keat Gin (A to Z guides, 2010)
The A to Z of Malaysia encapsulates the development of Malaysia from prehistory to the early years of the 21st century. It covers not only Malaysia's history but also its politics, economy, multiethnic society, multiculturalism, scientific and technological developments, and the state of its environment. A host of contemporary issues and challenges are featured, including ethnic polarization, economic equity, and polygamy; concepts like Ketuanan Melayu (Malay Dominance), "Malaysian Malaysia," "Malay," and Islam Hadhari (Civilizational Islam); and terms like "Ali Baba" business, kiasi, bejalai, and "Twenty Points." Over 500 cross-referenced dictionary entries are contained in this reference, covering everything from ethno-historical entries to those on culinary favorites and personalities. A chronology, an introductory essay, appendixes, and a bibliography complement the dictionary entries, enhancing the authoritative and up-to-date information provided.